HUBUNGAN DUKUNGAN SUAMI DENGAN KESIAPAN IBU BERSALIN DALAM KALA I PERSALINAN DI WILAYAH KERJA PUSKESMAS SEI LANGKAI KOTA BATAM - Siahaan, Dina Katrina; Sihombing, Sarmauli Franshisca (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2019)
Pregnancy is a physiological condition that every married couple dreams of. A baby who is born healthy and perfect is what every married couple has been waiting for. Waiting for the day of delivery can be a stressful and tiring experience. With the increasingly old gestational age, anything can happen to pregnant women before delivery. The purpose of this study was to determine the factors related to maternal readiness during the 1st stage of labor. This type of research was an analytic survey with a cross sectional design, with a total of 32 women giving birth, the sample was taken using the accidental sampling technique in February-August 2019 in the work area of the Sei Langkai Community Health Center, Batam City. The results of the research were 19 people (59.4%) lacking knowledge. Husband's support was negative as many as 18 people (56.2%). Support for negative health workers was 16 people (50.0%). The readiness of mothers during the first stage of labor was less than 17 people (53.1%). The conclusion of the chi-square test results shows that the p value = <0.05, meaning that there is a relationship between knowledge, support from husbands and support from health professionals on the readiness of mothers to give birth during the 1st stage of labor. Suggestions to respondents to increase their knowledge by seeking information and following health counseling held by health workers related to the readiness of mothers to give birth during the 1st stage of labor.